HBV and the importance of TLR9 on B cell responses - Issam Tout; Marie Marotel; Isabelle Chemin; Uzma Hasan (AIMS Allergy and Immunology, 2017)
Chronic HBV infection affects more than 240 million people worldwide and is a major risk factor for developing cancer in which 10–30% of cases will progress towards liver cirrhosis and hepatocellular carcinoma. Infection outcome relies on the immune system maturity. Toll-like receptor 9 (TLR9) is a sensor of viral and bacterial DNA motifs and activates plasmacytoid dendritic cells (pDCs) and B cells to generate effective immune responses against infection. B cells, especially CD38hi plasma cells play a major role in mediating humoral immune responses to clear HBV infection. Many studies have shown that TLR9 function is abrogated by HBV in pDCs. We aim to discuss the importance of B cell function in CHB patients and summarize concisely studies that describe the effect of HBV on TLR9 mediated B cell function. The effect of HBV on TLR9 activity in B cells should give insights into oncoviral immune escape strategies providing knowledge that will be essential to develop novel immunotherapeutic approaches.